2014
DOI: 10.1177/1933719113518992
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Changes During Menopause and the Impact on Fluid Regulation

Abstract: Reproductive surgeries leave women more susceptible to postoperative hypervolemic hyponatremia because during this period women can retain water at an accelerated pace and much faster than they do sodium. This review proposes that estrogen and progestogen exposure play an important role in the increased risk of hyponatremia in menopausal women. Estrogen and progesterone exposure have important effects on both body fluid regulation and cardiovascular function and both of these reproductive hormones impact blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 48 publications
8
54
0
2
Order By: Relevance
“…In addition, it has been reported that the fluid-regulating hormone, arginine vasopressin (AVP) is sensitive to slight increases in plasma osmolality, and it fluctuates by 0.41 pmol/L per unit change in plasma osmolality. Therefore, it is likely that AVP was stimulated by the elevation in serum osmolality in the isotonic beverage group, promoting the reabsorption of water by the kidney and resulting in better fluid retention [18,28,29]. Furthermore, C H2O —a good estimation of AVP responses—was lower with the isotonic beverage, resulting in lower urine output.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that the fluid-regulating hormone, arginine vasopressin (AVP) is sensitive to slight increases in plasma osmolality, and it fluctuates by 0.41 pmol/L per unit change in plasma osmolality. Therefore, it is likely that AVP was stimulated by the elevation in serum osmolality in the isotonic beverage group, promoting the reabsorption of water by the kidney and resulting in better fluid retention [18,28,29]. Furthermore, C H2O —a good estimation of AVP responses—was lower with the isotonic beverage, resulting in lower urine output.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that estrogen can explain the difference between the males and the females. First, estrogen has been demonstrated to play an important role in sodium–water homoeostasis (Stachenfeld, ) through influencing multiple processes. Second, the Na x channel acts as a sensor of the sodium concentration of the body fluid and can regulate salt‐intake behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Stachenfeld et al [54] reported that estrogen therapy retained body water in menopausal women to avoid dehydration. Thus, estradiol lowered the operating point for osmoregulation of arginine vasopressin and thirst and increased plasma volume [55]. However, it has been reported that spontaneous water consumption fluctuated during the estrous cycle [56].…”
Section: Discussionmentioning
confidence: 99%